On the constellation of early wild beekeeping terminology in Latvian and Sorbian - Eckert, Rainer (Baltistica, 2022)
In the article we have found a lingual connection between two voluminous fields of early terminology in the Baltic and Slavic languages, related to climbing up honey-trees and making beehives in the trees. An important role is played by the Sorbian and Latvian languages.
Keywords: Latvian; Sorbian; Baltic-Slavic comparison; phraseology; etymology; wild beekeeping